2021
DOI: 10.1042/bst20200329
|View full text |Cite
|
Sign up to set email alerts
|

The role of lactobacilli in inhibiting skin pathogens

Abstract: The human skin microbiota forms a key barrier against skin pathogens and is important in modulating immune responses. Recent studies identify lactobacilli as endogenous inhabitants of healthy skin, while inflammatory skin conditions are often associated with a disturbed skin microbiome. Consequently, lactobacilli-based probiotics are explored as a novel treatment of inflammatory skin conditions through their topical skin application. This review focuses on the potential beneficial role of lactobacilli (family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…4 Such strategies have not yet widely been considered for direct application on the skin, in a large part because of the technical challenges. 5 One of the most common skin diseases is acne vulgaris, a chronic inflammatory skin condition of the sebaceous follicles and glands. The pathogenesis of acne vulgaris is multifactorial, with increased sebum production, alteration in the quality of sebum lipids, dysregulation of the hormone environment, and follicular hyperkeratinization as contributing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Such strategies have not yet widely been considered for direct application on the skin, in a large part because of the technical challenges. 5 One of the most common skin diseases is acne vulgaris, a chronic inflammatory skin condition of the sebaceous follicles and glands. The pathogenesis of acne vulgaris is multifactorial, with increased sebum production, alteration in the quality of sebum lipids, dysregulation of the hormone environment, and follicular hyperkeratinization as contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Such strategies have not yet widely been considered for direct application on the skin, in a large part because of the technical challenges. 5 …”
Section: Introductionmentioning
confidence: 99%
“…These are both diverse families that include species closely associated with humans, e.g. as part of the human skin, respiratory tract or gut microbiome (Cogen et al , 2008; Fierer et al , 2008; Murphy and Parameswaran, 2009; Kim et al , 2013; Fourquin-Gomez et al , 2014; Robert-Pillot et al , 2014; Rock and Donnenberg, 2014; Delanghe et al , 2021; Skowron et al , 2021), but have also been isolated from animal hosts and soil and aquatic environments (Cousin, 1999; Madhaiyan et al , 2020). Other families were detected in significant abundance, but only in subsets of samples, such as Vibrionaceae and Lactobacillaceae (in 21 and 30 samples out of 42 respectively).…”
Section: Resultsmentioning
confidence: 99%
“…1B) including families found before in humans and human-associated environments, e.g. the human skin, gut or respiratory tract microbiome, or human food production (Cogen et al , 2008; Fierer et al , 2008; Murphy and Parameswaran, 2009; Oren, 2011; Fourquin-Gomez et al , 2014; Delanghe et al , 2021; Skowron et al , 2021). The evidence from our data set that community composition varied depending on the shop type in which each banknote was collected is surprising: this suggests money has a microbiome reflecting its local environment, even though we assume banknotes are only transiently exposed to each habitat/shop type.…”
Section: Discussionmentioning
confidence: 99%
“…Another antimicrobial mechanism indicated by co-aggregation is competitive displacement of the pathogen with some LAB strains showing high affinity binding to epithelial cell receptors (Lukic et al, 2017;Spacova et al, 2020). Several studies demonstrate antimicrobial effects of LAB on S. aureus (Blanchet-Réthoré et al, 2017;Jayashree et al, 2018;Spacova et al, 2020;Delanghe et al, 2021;Musa et al, 2021) and recent findings indicate, that aggregation of lactobacilli to S. aureus is important for the ability of lactobacilli to prevent or reduce S. aureus adhesion to epithelial surfaces (Younes et al, 2016). Previous study has shown that topical application of LAB in a cream formulation can have beneficial effect on AD symptoms and S. aureus colonization on skin (Blanchet-Réthoré et al, 2017;Butler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%